Faktor Faktor Yang Mempengaruhi Dalam Upaya Peningkatan Pembayaran PBB Tahun 2022 Di Kecamatan Peterongan - Zainul Arifin; Nieke Nurdiyanty Winanda; Shobirin Noer (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
Taxes as one of the sources of state income have an important function, namely as a source of funds for the government to finance its expenses and taxes also as a tool for regulating and exercising government discretion in the socio-economic field. (Mardiasmo, 2017). In raising public awareness, it is necessary to socialize that promotes public consciousness. Thus, socialization is one of the factors that affect the compliance of the taxpayer of the building earth. The research method used is Qualitative Descriptive, using Informants in this study are Village Government Apparatus and community leaders. The results of the study show that what factors influence in the efforts to increase UN payments in 2022 In Peterongan District it can be concluded that the internal environment includes. human resources, financial resources as well as means and infrastructure